Competitiveness of Indonesian Eel (Anguilla sp) in International Market - Arif Yustian Maulana Noor; Zainal Abidin (Faculty of Fisheries and Marine Science, Brawijaya University, 2019)
This study aims to analyze the competitiveness of Indonesian eel in the international market both comparative and competitive advantage. This type of research data is secondary data sourced from the United Nations Nation Database. The data analysis method uses Revealed Symmetric Comparative Advantage (RSCA), Export Product Dynamics (EPD) and Hirschman Herfindahl Index (HHI). Eel is a fishery commodity that has a potential export market. China is the main exporter of eel in the world with a share of 64%. Some EU member countries are still carrying out international trade in eel although CITES has included it in Appendix II as a protected species. The export of Indonesian eel consists of life, fresh and frozen. The comparative competitiveness of live and frozen eel is quite good while fresh eel is still low. The competitive advantage of Indonesian eel in the international market is still in the falling star quadrant. The concentration of the global eel market is based on the Herfindahl index that frozen eel is unconcentrated, it is mean that frozen eel is the most potential to be developed as an export commodity.